2010
DOI: 10.1016/j.jesp.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Need for Cognition and the process of lie detection

Abstract: Four experiments investigated the influence of Need for Cognition on the process of lie detection. According to the basic assumptions of dual process models, only higher Need for Cognition leads to the use of verbal information when making judgments of veracity. People with lower Need for Cognition predominantly use stereotypical nonverbal information for their judgments. In both Experiments 1 and 2, participants saw a film in which nonverbal cues (fidgety vs. calm movements) and verbal cues (low vs. high plau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 47 publications
5
77
2
1
Order By: Relevance
“…Visual cues are easier to process and require fewer cognitive resources; therefore, they can be processed heuristically (Reinhard, ; Reinhard & Sporer, , ; Stiff, Miller, Sleight, Mongeau, Garlick & Rogan, ). Verbal cues require greater cognitive resources (Gilbert & Krull, ); therefore, analytical processing is needed to process these cues (Chaiken, ; Reinhard, ; Reinhard & Sporer, ). If the truth bias results from heuristic processing, then visual cues should yield more of a truth bias than verbal cues (Burgoon, Blair & Strom, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual cues are easier to process and require fewer cognitive resources; therefore, they can be processed heuristically (Reinhard, ; Reinhard & Sporer, , ; Stiff, Miller, Sleight, Mongeau, Garlick & Rogan, ). Verbal cues require greater cognitive resources (Gilbert & Krull, ); therefore, analytical processing is needed to process these cues (Chaiken, ; Reinhard, ; Reinhard & Sporer, ). If the truth bias results from heuristic processing, then visual cues should yield more of a truth bias than verbal cues (Burgoon, Blair & Strom, ).…”
Section: Methodsmentioning
confidence: 99%
“…If the truth bias results from heuristic processing, then visual cues should yield more of a truth bias than verbal cues (Burgoon, Blair & Strom, ). Further, because analytical processing takes a systematic approach towards forming judgments, accuracy should be higher when verbal cues (processed analytically) are available (Reinhard, ; Reinhard & Sporer, ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, when individuals' cognitive resources are reduced (e.g., by an ego depletion task), they experience more difficulties to analyze verbal cues and achieve lower detection accuracy (Reinhard, Scharmach, & Stahlberg, 2013). Similarly, individuals with high need for cognition (i.e., with a higher motivation to engage in effortful cognitive endeavors) do engage in systematic information processing when facing low (vs. high) cognitive load and are better at detecting deception (Reinhard, 2010). This study aims at extending those results to assess the actual impact of measured cognitive ability.…”
Section: Cognitionsmentioning
confidence: 99%
“…Restricting judges to non‐verbal cues (in video‐only presentations) for their judgments seems to have impaired their ability to discriminate lies from truths. Accordingly, Reinhard (2010) found that judges’ cognitive motivation moderates classification accuracy for true and deceptive messages. The higher judges’ cognitive motivation, the more they used verbal cues of deception and therefore achieved higher classification accuracy for true and deceptive messages.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that the reliance on verbal content cues in deception detection is a reliable moderator of classification accuracy. In a series of experiments, Reinhard and his colleagues have shown that a more pronounced (self‐reported) use of verbal content information in contrast to non‐verbal behavior leads to a higher accuracy at discerning lies and truths (Reinhard, 2010; Reinhard, Sporer, Scharmach, & Marksteiner, 2011; see also Mann, Vrij, & Bull, 2004). Further, in a recent comprehensive meta‐analysis on deception detection accuracy, Bond and DePaulo (2006) found higher accuracy rates for messages in audio‐visual presentations, audio‐only presentations or transcripts, where judges have access to verbal deception cues, than for messages in video‐only presentations, where judges are confined to non‐verbal behaviors as deception cues.…”
Section: Introductionmentioning
confidence: 99%